Analysis of errors in solving mathematical literacy analysis problems using newman - Neneng Nuryati; Siti Syamsiah Purwaningsih; Endang Habinuddin (International Journal of Trends in Mathematics Education Research, 2022)
The purpose of this study was to find out student errors in solving problems about mathematical literacy. This study uses a qualitative research approach with sampling method is purposive sampling. The study subjects were three students who were taken based on KAM (Student Initial Ability), namely high, medium, and low ability categories. Each subject is one person per category from the Department of Accounting, Bandung State Polytechnic. This study analyzes student errors in solving mathematical literacy problems in the statistics course for the sub-discussion of hypothesis testing. The error analysis method used is Newman analysis. This study uses two instruments, namely a test instrument with four questions in the form of descriptions and interviews. The data will then be classified into five error categories according to Newman's analysis. The conclusions in this study indicate that there are errors in answering questions, especially for mathematical literacy questions; students are expected to be able to analyze questions in the form of story questions; Understanding the problem instructions and information contained in the problem is the first step in working on mathematical literacy problems so that the level of errors and errors in working on the questions is more resolved. Of the five errors that became the standard for Newman Error Analysis assessment, three errors were made by respondents, namely errors in understanding story questions correctly, errors in transforming story questions into mathematical sentences, and errors in writing the final answer.